The influence of training on attitude towards people with mental disorder in a sample of university students - Yolanda Medina-Mesa; Serafín Jesús Cruces-Montes; Ana Merchán-Clavellino; Antonio Francisco Romero-Moreno; Rocío Guil-Bozal (INFAD, 2019)
The prevalence of mental disorders in primary care has been the subject of numerous studies and is between 24 and 30% in our environment. However, only between one third and half of the cases are correctly recognized by the Primary Care physician, no differences were found in attitudes or knowledge between Primary Care physician with training via MIR (Interim Resident Physician) and non-MIR, despite the fact that the MIR training program includes mental health training. Different professionals find interaction situations with these patients in their daily performance and may act as stigma perpetuators if they show negative attitudes of fear and hostility (Roos and Goldner, 2009). The aim of this study was to examine if the training during the university degree changes the attitudes towards people with mental disorder in the future professionals of Health Sciences and Social and Legal Sciences. The questionnaire “Opinions concerning mental illness” (Ozamiz, 1980) was administered to 820 students (70.37% women and 29.63% men) from different degrees of Health Sciences, and Social and Legal Sciences. This scale assessed global Attitude and five subscales (Negativism, Social Etiology, Authoritarianism, Restrictivism, and Prejudice), obtaining a reliability higher than .7 in Negativism and Social Etiology. Results indicated that students in their final year of Health Sciences as well as Social and Legal Sciences, show attitudes more positive, lower levels of Negativism towards mental ill patients and greater tolerance than first-year students. In addition, first-year students of the degrees linked to Health Sciences have a more positive attitude, less Negativism and greater tolerance towards mentally ill patients, compared to the first-year students of degrees related to Social and Legal Sciences, indicating the possible vocational influence in the election of sanitary qualifications.